Effect of heat treatment on interface behavior of martensite/austenite multilayered composites by accumulative hot roll bonding. Issue 12 (2nd December 2019) - Cao, Rui; Ding, Yun; Yan, Yingjie; Zhang, Xiaobo; Chen, Jianhong
ABSTRACT: The 2Cr13/316L multilayered steel (MLS) composites were prepared by accumulative hot roll bonding and heat treatment. The element diffusion, interface bonding mechanism and interface bonding properties of the MLS composites were investigated. The microstructures of the MLS composites before and after heat treatment, are mainly composed of austenite (A), martensite (M), ferrite (F) and little M23 C6 carbides. The grain refinement is achieved by accumulative hot roll bonding and heat treatment. The bonding mechanism can be divided into diffusion and recrystallization based on the difference of formation of interfacial grains. The heat treatment has opposite effects on bending strength and shear strength, it is because that softening and interface enhancement of heat treatment have different effects on corresponding bending and shear fracture behavior.